2003
DOI: 10.1021/jf034278x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Astragalus in China:  Molecular Evidence from the DNA Sequences of 5S rRNA Spacer, ITS, and 18S rRNA

Abstract: Radix Astragali (root of Astragalus; Huangqi) is a traditional Chinese medicine commonly used as an immunostimulant, hepatoprotective, diuretic, antidiabetic, analgesic, expectorant, and sedative drug. Although the species of Radix Astragali have been defined as Astragalus membranaceus and A. membranaceus var. mongholicus in Pharmacopoeia of China, their taxonomy remains controversial. The phylogenetic relationships among 10 Astragalus taxa, which are commonly found in China including A. membranaceus, A. membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 15 publications
4
37
0
1
Order By: Relevance
“…Such diversity makes it difficult to unambiguously delimit species in this complex. For example, some workers kept specific status for A. membranaceus and A. mongholicus (Komarov, 1946;Shi, 2003;Zhao, 2006;Zhang et al, 2009), whereas more studies merge them as one species (Hsiao, 1964;Chen and Zhu, 1990;Ho and Fu, 1993;Dong et al, 2003;Zhu, 2003;Liu, 2008;Qian et al, 2009;Xu and Podlech, 2010). Hsiao (1964) attribute such morphological diversity to adaptation to different habitats, and "A. membranaceus and A. mongholicus tend to be undistinguishable when habitats are convergent".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such diversity makes it difficult to unambiguously delimit species in this complex. For example, some workers kept specific status for A. membranaceus and A. mongholicus (Komarov, 1946;Shi, 2003;Zhao, 2006;Zhang et al, 2009), whereas more studies merge them as one species (Hsiao, 1964;Chen and Zhu, 1990;Ho and Fu, 1993;Dong et al, 2003;Zhu, 2003;Liu, 2008;Qian et al, 2009;Xu and Podlech, 2010). Hsiao (1964) attribute such morphological diversity to adaptation to different habitats, and "A. membranaceus and A. mongholicus tend to be undistinguishable when habitats are convergent".…”
Section: Resultsmentioning
confidence: 99%
“…A few molecular phylogenetic study lent some supports to above-mentioned revisions (Dong et al, 2003;Zhang et al, 2009), which indicated three species of A. penduliflorus complex (A. membranaceus, A. mongholicus and A. propinquus B.Schischk. ) formed a clade.…”
mentioning
confidence: 81%
“…However, human activities and increased utilization in TCM have caused a dramatic decline in the natural populations in the last few decades. Although the morphology, karyotype, molecular phylogeny, pharmacology and metabonomics of A. mongholicus have been extensively studied [3,[6][7][8][9], information on population genetics is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This plant has been used widely in traditional Chinese medicine to tonify the "Qi" (vital energy) and is prescribed to treat symptoms such as fatigue, lack of appetite, frequent colds, spontaneous sweating and shortness of breath. 1 Pharmacological studies have revealed it to have antiviral, 2 hepatoprotective, 3 antioxidant, 4 cardiovascular protective 5 and immunostimulant activity. 6 In addition, Radix Astragali has been reported to increase the resistance to the immunosuppressive effects of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%